2013
DOI: 10.1007/s00467-012-2385-4
|View full text |Cite
|
Sign up to set email alerts
|

Low expression of glucocorticoid receptors in children with steroid-resistant nephrotic syndrome

Abstract: Patients with initial SRNS showed decreased GR expression in peripheral blood mononuclear cells (PBMC) before starting therapy, and this low expression may be one of the pathophysiological mechanisms of steroid resistance in these children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
17
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 20 publications
2
17
0
Order By: Relevance
“…In agreement with our study, Hammad et al (2013) (15) found that 65% of SRNS were males and Shah et al (2015) (16) found that 66.7% of their SRNS patients were males.…”
Section: Discussionsupporting
confidence: 93%
“…In agreement with our study, Hammad et al (2013) (15) found that 65% of SRNS were males and Shah et al (2015) (16) found that 66.7% of their SRNS patients were males.…”
Section: Discussionsupporting
confidence: 93%
“…Bagdasorova et al 13 found an increase in GCR expression in patients with steroid sensitive and decrease in steroid resistance NS. Similar results were obtained by Ayman et al, 14 who found lower GCR expression on lymphocytes in steroid resistance NS in comparisons to steroid sensitive NS and control. Han et al 15 showed that glomerular GCR expression was significantly lower in late than in early steroid responder adults with NS.…”
Section: Discussionsupporting
confidence: 80%
“…Ghobrial et al, [14] found that 85% of the SSNS group, 75% of the SDNS group and 90% of the SRNS group were males. Hammad et al, [15] found that 65% of SRNS were males and Shah et al [16] found that 66.7% of their SRNS patients were males. There was no significant difference between the subgroups of nephrotic patients regarding sex (p-value = 0.057).…”
Section: Resultsmentioning
confidence: 99%